Colour tunable cool pigments based on TiZn2O4 inverse spinels. Issue 16 (27th July 2022) - Joshy, Deepak; Jijil, Chamundi P.; Jose, Sheethu; Ismail, Yahya A.; Periyat, Pradeepan
Abstract : Eco-friendly and cost-effective colour tunable TiZn2 O4 inverse spinel based NIR reflecting pigments. Abstract : A new class of near-infrared (NIR) reflecting yellow and orange cool pigments based on TiZn2 O4 inverse spinels were synthesized. The colour tuning in pure TiZn2 O4 was made possible by the substitution of octahedral Zn 2+ ions by Cu 2+ and Fe 3+ ions separately. By the incorporation of Cu 2+ and Fe 3+ ions into the inverse spinel lattice in varying amounts, a series of pigment compositions having colours ranging from greenish-yellow to reddish-brown was obtained. The developed pigments exhibited moderate to high NIR reflectance ranging from 47.61 to 87.81%. The TiZn2 O4 based NIR reflecting pigment provided an interior 4.8 °C cooler than an uncoated roofed interior. Cu 2+ and Fe 3+ doped TiZn2 O4 systems were found to be highly stable and eco-friendly cool pigment candidates capable of achieving better thermal conditioning and impressive energy conservation.